Biochemical Analysis of Ovarian Follicular Fluid in Dairy Cattle with Anatomical Defects in the Genitalia - V.R. Annie; K.M. Lucy; N. Ashok; S. Maya (Indian Journal of Veterinary Anatomy, 2024)
Biochemical constituents in the follicular fluid were compared using the ovaries of 100 dairy cows / heifers collected from the Meat Technology Unit, Mannuthy. Among the 100 animals, 14 animals showed anatomical defects in the genitalia. The anatomical defects noticed on the reproductive system were categorized as ovarian hypoplasia, tubal obstruction, uterus unicornis, bicornis bicorpus unicollis and kinked cervix. Sodium, potassium and chloride content in the follicular fluid were measured using electrolyte analyser. Commercial kits were used for the measurement of copper, zinc, triglycerides, urea, nitrogen, total protein and cholesterol. Iron, phosphorus and magnesium were determined colourimetrically using standard kits and measured by using multimode micro/ELISA plate reader and plate washer. While comparing the biochemical constituents in the follicular fluid of animals having anatomical defects with the control value, mean concentrations of potassium, triglycerides, urea, nitrogen and magnesium were significantly higher in the follicular fluid of animals having anatomical defects. The concentration of zinc also exhibited a significant difference but the mean concentration was less in animals having anatomical defects. The average level of cholesterol, copper and phosphorus was observed higher in the follicular fluid of animals having anatomical defects. Concentration of total protein and iron was found almost similar with the reference value. Changes in the biochemical composition of follicular fluid might influence oocyte quality and preparation of the follicle for subsequent corpus luteum formation and its functioning.